New Scuttle flies (Diptera: Phoridae) reared from dead Termite, Odontotermes formosanus (Shiraki, 1909) (Isoptera: Termitidae) in China - Liu, Guang-Chun; Chen, Gao (Zootaxa, 2019)
Two scuttle flies, Megaselia nigrifinis sp. n. and M. setidifferitatis sp. n. are described and illustrated. The flies were reared from dead termite, Odontotermes formosanus (Shiraki, 1909) (Isoptera: Termitidae) in Nanjing, China.